Curbing Price Fluctuations in Cap-and-Trade Auctions - Thomas D. Jeitschko; Pallavi Pal (Center for Economic Studies and ifo Institute (CESifo), 2022)
In recent years, a significant problem with the carbon credit market has been higher than initially predicted price volatility. It is essential to study the market in a repeated-period dynamic setting to identify the factors enabling high fluctuations in prices. In this paper, we examine the dynamic auction design and propose a method to curb price volatility through a flexible supply cap. The equilibrium analysis shows that modifying the cap on per period supply can decrease price fluctuations. Currently, the government or the auctioneer sets a per-period limit on the supply, which reduces at a fixed rate over time. However, this paper suggests that a flexible cap on the per-period supply would be a better alternative. Specifically, we show that correlating the supply rate with expected future demand results in a more stable price.
Keywords: D43; L11; L42; 330; dynamic mechanism design; auctions; emissions permits; environmental regulation; climate change